(3GdCfhGQ GdHgjI Ydi NWHI TQM GdbWH GdTeSjIs - (3CMeO Hf YHO GdaJGM GdTGaYj Gdedhis; (3GdbWH GdJMJGfj , eMeO (B( (3eMehO (B) (3Hf eMeO GdQGRj, CHh YHO Gddg, bWH GdOjf CHh YHO Gddg GdJMJGfj,J (B766 (3g` s
(3ChdgG (B:s
(3hHYO ajbhd GdYHO GdabjQ Edi QHg Gdbhi CMeO Hf YHOGdaJGM GdTGaYi Gdedhi s
(3BNQgG (B:s
(3GdJMbjb Ci EKHGJ GdTF HOdjdg Ch PcQ GdTF Ydi GdhLg GdMb s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH GdChds
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3MQjQ GdbhGYOGdefWbjI gh TQM Ydi GdTeSjI hGdJi gi ddcGJHi hGdbRhjfi GfXQ cTa GdXfhf L (B2 (3U` (B1063s
(3EjVGM Gdecfhf L(B2 (3U`(B56 s
(3YdjgG Jedc ddTjN TeS GdOjf eMeO GdLhgQi GdTGaYi s
(3JHUQI GdYfhGf (B:s
Keywords: (3GdadSaI hGdefWbs